Analysis of landscape structure of the Braço River sub-basin as subsidy for a project of Payment for Ecosystem Services in the city of Camboriu, Santa Catarina, Brazi - Antunes, Pedro Paulo; Carvalho, Rosemeri Marenzi; Espinoza, Helia Del Carmen Farias (Sociedade & Natureza, 2017)
Landscape Ecology has become an important tool for decision-making in the planning of land use. The aim of this study was to analyze land use and land cover of the Braço River hydrographic sub-basin, as support for the Projeto Produtor de Água (Water Producer Project). This initiative is being introduced in the municipality of Camboriú, in the State of Santa Catarina for PSA (Payment for Ecosystem Services). Geoprocessing Technologies were used, namely: satellite imaging (Quickbird) and Geographic Information Systems (Spring 5.2.4 and ArcGis 10). The analysis of land use and land cover indicates a prevalence of Medium and Advanced Stage Forest (74.04% of the sub-basin). Between elements of the landscape, the patch Medium and Advanced Stage Forest was the most significant, and is therefore the landscape matrix. However, connectivity may be prejudiced by fragmentation, due to the lack of corridors in the Permanent Protect Areas (APPs) along the margins of water courses, and the presence of the highway system as barriers. This methodology enables to obtained a profile of the landscape and detect the need for planning of this use, based on principles of Landscape Ecology, with a focus on connectivity of land fragments.